Od Maribora do Bele krajine: priročnik za terensko spoznavanje Slovenije - Vovk Korže, Ana (2018)
From Maribor to Bela krajina: a Guide to Field Recognition of Slovenia. Bela krajina is the Southeastern region of Slovenia. Beside the distinct karst charachteristics Bela krajina is geologically a part of Slunj plate, which is why it is also known as an equator. Its openness to East enables direct influences from the Pannonian Basin and Kvarner. The geographical diversity of the area attracts many visitors. The manual presents pannonian, alpine and karst regions that we can observe on our journey from Maribor to Bela krajina. The descriptions of the regions are geographically oriented and there is an ephasis on natural geographical factors. These factors include geological and lithological base, waters, climate, soil and vegetation. Soil managment as a result of interlacement of natural and social charachteristics is the most visible element of the region. Coauthors of the contributions about individual regions are geography students. The students were updating their knowledge about the region on the field within the course  called Geography of Slovenian regions.
Keywords: Bela krajina; Southeast Slovenia; low karst; Kolpa river; Črnomelj